Upaya Meningkatkan Kualitas Hasil Belajar IPA Materi Struktur Dan Fungsi Tumbuhan Melalui Model Direct Instruction (DI) Pada Siswa Kelas VIII Semester Ganjil SMP Negeri 1 Simpang Teritip Tahun Pelajaran 2022/2023 - Nunung Farida (STIKes Ibnu Sina Ajibarang, 2023)
Based on the findings of class VIII junior high school students, the results showed that class VIII students were still minimally introduced to scientific work, in accordance with the Science Education Content Standards, scientific work is an important characteristic of science learning subjects and of the 26 students the level of mastery of the material only reached 26.93. %. Identifying the problems raised, the author tries to improve learning by conducting research applying the Direct Instruction (DI) Model. Based on the learning results during the learning activities, the author formulates the problems that arise and discusses them with supervisor 2 to find the causes and problems identified above. The problem in improving this learning is formulated as follows: Can the Application of the Direct Instruction (DI) Model Improve Learning Outcomes in Science Learning Material on Plant Structure and Function in Class VIII Odd Semester of SMP Negeri 1 Simpang Teritip for the 2022/2023 Academic Year? From the improvement activities of Cycle I, the following results were obtained: 3 students who got a score less than 40 - 55 (11.54%), 10 students who got a score greater than 56 - 66 (38.46%) and There were 13 students who got a score greater than 67 – 79 (50.00%). In cycle II, there were 9 students who got a score less than 56 - 66 (34.62%), 16 students who got a score greater than 67 - 80 (61.54%), students who got a score greater than 81 – 100 as many as 1 person (3.84%). In Cycle III, it showed that of the 26 students studied, 3 people (11.54%) got a score of less than 75, while 23 students got a score of more than 75 (88.46%). The average student score increased by 86.15 - 73.46 = 12.69. Increased 12.69% compared to cycle II. The conclusion from writing this PTK is that the correct application of the Direct Instruction (DI) Model can improve learning outcomes.